2019
DOI: 10.1021/acs.jpcb.8b11677
|View full text |Cite
|
Sign up to set email alerts
|

Localized pH Pulses in PBS Buffer Repeatedly Induced by Visible Light

Abstract: The pH of biological systems is important for the activity of enzymes, and abnormal cellular pH is related to many diseases. Spatial and temporal modulation of pH with light will be useful for studying the pH effects on enzymatic functions and disease mechanisms and may lead to new drug delivery and therapeutic methods. However, the pH of biological systems is maintained by pH buffers, which implies that only temporary pH change (pH pulse) can be induced in an open system. A key fundamental problem is whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…It is worth mentioning that the pH of biological systems is often maintained by pH buffers. However, temporary and reversible pH change can be locally produced by localized mPAHs, which can be achieved by polymerizing mPAHs 44,51,52 or encapsulating mPAHs in nanomaterials. 23,38 For example, our group showed that pH pulses of ∼1.7 units can be repeatedly generated in a micrometer film of an mPAH hydrogel in PBS.…”
Section: Coupling Mpahs With Functional Systemsmentioning
confidence: 99%
“…It is worth mentioning that the pH of biological systems is often maintained by pH buffers. However, temporary and reversible pH change can be locally produced by localized mPAHs, which can be achieved by polymerizing mPAHs 44,51,52 or encapsulating mPAHs in nanomaterials. 23,38 For example, our group showed that pH pulses of ∼1.7 units can be repeatedly generated in a micrometer film of an mPAH hydrogel in PBS.…”
Section: Coupling Mpahs With Functional Systemsmentioning
confidence: 99%
“…Photoacid 1 (PA1) was discovered during a systematic study of indazole type mPAHs. [34,37,38] Indazole mPAHs function at physiological pH and have shown potential in biomedical area. A indazole mPAH was recently utilized to change the intracellular pH environment in an anticancer study.…”
Section: Resultsmentioning
confidence: 99%
“…[34] A polymer of a indazole photoacid was shown to be able to generate pH pulses in PBS buffer under irradiation. [38] The structure, synthesis, and photoreaction of PA1 are shown in Figure 1. PA1 was conveniently synthesized by coupling a methyl benzothiazolium with a indazole aldehyde.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations